THE EFFECT OF THREE PRETREATMENTS ON BREAKING SEED DORMANCY OF BAOBAB (ADANSONIA DIGITATA L.) - KA, BASHIR; DD, MUSA; R, BISHIR (Innovare Journal of Agricultural Sciences, 2021)
Objective: Baobab (Adansonia digitata) is a native tree that is found in African savannas, it is a member of family ‘Malvaceae’. The tree is found in Nigeria, South Africa, Botswana, Namibia, Mozambique and in different regions of western Madagascar. Seed dormancy is the most limiting factor for some plants propagation. Dormancy allows seeds to separate from their mother plant and survive dispersal, over distance, and time before growth recommences. This study was aimed to determine the effect of three pre-treatments on breaking the seed dormancy of Adansonia digitata L., a multi-purpose and indigenously endangered tree. Methods: The study was carried out in the greenhouse of the Department of Biological Sciences, Federal University Dutsin-Ma, Nigeria. The three pre-treatments are: Soaking in hot water (100°C) for 5, 10, 15, and 20 min; and soaking in sulfuric acid (H2SO4) and hydrochloric acid (HCL) concentrations (100%, 75%, 50%, and 25%) for 5, 10, 15, and 20 min. Untreated seeds served as control. These were laid out in a complete randomized design with three replications. Data were collected on germination percentage, germination rate, day of emergence, and the average seedlings height. Results: The result showed that earliest mean days of emergence (7 days) were observed in seeds subjected to hot water treatment at 15 min. It also showed the highest rate of germination and percentage 6 (100%). On the other hand, the effect of acids (H2SO4 and HCL) pre-treatments on the seeds gave a fair result (16.66–33.33%), untreated seeds did not germinate. Conclusion: All the pre-treatments used in the study were found to be effective. However, soaking of seeds in hot water (100°C) pre-treatment for 15 min is recommended for breaking the seed dormancy of A. digitata.